You're Killing the Mountain- Eight Artistic Projects on the WATER and TERRAINS of Murree, Pakistan | 2017 (MMARF, 2017)
Murree Museum Artist Residency.
English
Keywords: Art- Nature; Artist Residency; N4390-5098 Visual Arts- Exhibitions; Pakistan